PENGARUH TOKOH AGAMA TERHADAP PERILAKU KEAGAMAAN REMAJA DESA KASIH RAJA KABUPATEN OGAN ILIR - Aldo Saputra; Emi Puspita Dewi (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
The aim of this research was to determine the influence of religious figures on the religious behavior of teenagers in Kasih Raja Village, Ogan Ilir Regency. This research uses quantitative methods, with independent (X) religious figures and dependent variable (y) adolescent religious behavior. With a population of 377 village teenagers and a sample of 79 teenagers with an age range of 12-21 years, the research used the SPSS version 26 program. The results of the study showed that the calculated t value was 0.0627 and the t table value was 0.1864. This means that the calculated t value is > the t table value, so it can be said that Ho is accepted because the calculated t value is greater than the t table value. From the results of this research, it can be concluded that religious figures influence religious behavior.